PotN represents a novel energy‐state sensing PII subfamily, occurring in firmicutes. (24th March 2022) - Iskhakova, Zalina I.; Zhuravleva, Darya E.; Heim, Christopher; Hartmann, Marcus D.; Laykov, Aleksandr V.; Forchhammer, Karl; Kayumov, Airat R.
Abstract : PII proteins are signal processor proteins that regulate the cellular metabolism of Bacteria, Archea and plant chloroplasts typically in response to the cellular nitrogen status. Here, we report the first biochemical characterization of a novel PII‐like protein PotN from Lentilactobacillus hilgardii . PotN is encoded in an operon together with the potABCD genes, encoding the ABC transporter for spermidine/putrescine. Like canonical PII proteins, the native PotN has a trimeric structure and competitively binds ATP and ADP, but it does not bind 2‐oxoglutarate. Immunoprecipitation and pull‐down experiments revealed that PotN is associated in vivo with the transcriptional regulator GlnR and the beta‐subunit of pyruvate/2‐oxoglutarate/acetoin dehydrogenase AcoB. Moreover, in vitro assays revealed that the ATPase domain of PotA also is able to interact with PotN. Interaction analyses demonstrated that PotN preferentially associates with PotA in the ADP state, whereas it binds to GlnR at elevated ATP levels. This suggests that PotN regulates the transport of polyamines and GlnR‐dependent gene expression in response to the energy availability for the cell. Abstract : We report the first biochemical characterization of a novel PII‐like protein PotN from Lentilactobacillus hilgardii . PotN competitively binds ATP and ADP. In the ADP state, PotN preferentially associates with the ATPase domain of PotA, whereas in the ATP state, it binds to transcriptional regulator GlnR. This suggests that PotN regulates the transport of polyamines and GlnR‐dependent gene expression in response to the energy availability in the cell.